(untitled) (Orthodontic Journal of Nepal, 2015)
Introduction: Malocclusion is the improper relationship of maxillary and mandibular teeth. The prevalence of malocclusion varies in different populations of the world. Objective: To study the prevalence of malocclusion in western part of Nepal and to evaluate the gender variation in occurrence of malocclusion. Materials & Method: A total of 1284 subjects were studied. Out of them 656 were male and 628 were female. Intra-oral examination was carried out to assess occlusal types of Class I, II, III according to Angle’s classification of malocclusion, and various occlusal characteristics like crowding, spacing, cross-bite, open-bite and deep bite were recorded. Gender variation in malocclusion characteristics were tested using chi-square test (p<0.05). Result: The present study showed that Class I occlusion type with malocclusion was more prevalent than Class II and Class III malocclusions. Class I was seen in 71.5% , Class II div 1 in 20.7%, Class II div 2 in 3.9% cases and Class III in 4.1% cases. Among the occlusal characteristics; crowding (61.3%), deep bite (29.5%) and spacing (10.5%) were most prevalent. Conclusion: Class I malocclusion was most prevalent type of malocclusion in western Nepalese subjects. There was no significant gender dimorphism between male and female in prevalence of various malocclusion characteristics.